2007
DOI: 10.1016/j.clim.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell activation and maturation induced by mucosal fluid from women with bacterial vaginosis

Abstract: Dendritic cells (DC) at mucosal surfaces mature when exposed to "danger" signals such as LPS. Bacterial vaginosis (BV) is a prevalent alteration of the vaginal bacterial flora associated with preterm childbirth and increased risk for HIV acquisition. We examined the effect of mucosal fluid from women with BV or healthy flora on DC function. IL-12, IL-23 and p40 production by monocytederived dendritic cells (MDDC) were all induced by BV samples. Activation/maturation markers HLA-DR, CD40, and CD83 on MDDC incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 65 publications
3
20
1
2
Order By: Relevance
“…Because increased IL-6 and IL-8 levels are only found in women with BV and not in women with normal flora, it indicates that, of the former two possibilities, the production site of these cytokines rather is the vagina and not the endocervix. In fact, studies already showed that vaginal fluids from women with BV are more stimulatory on activating the cytokine cascade in vitro when compared to vaginal contents from the normal flora [30,31]. Finally, the current findings showing that levels of proinflammatory cytokines are unchanged in the normal flora, even in the presence of CT, reinforcing the importance of maintaining a lactobacillidominated vaginal flora for protecting against STI acquisition.…”
Section: Resultssupporting
confidence: 71%
“…Because increased IL-6 and IL-8 levels are only found in women with BV and not in women with normal flora, it indicates that, of the former two possibilities, the production site of these cytokines rather is the vagina and not the endocervix. In fact, studies already showed that vaginal fluids from women with BV are more stimulatory on activating the cytokine cascade in vitro when compared to vaginal contents from the normal flora [30,31]. Finally, the current findings showing that levels of proinflammatory cytokines are unchanged in the normal flora, even in the presence of CT, reinforcing the importance of maintaining a lactobacillidominated vaginal flora for protecting against STI acquisition.…”
Section: Resultssupporting
confidence: 71%
“…Certain bacterial products, particularly from anaerobes, have been shown to result in induction of proinflammatory cytokine production through TLR stimulation [79], dendritic cell activation and maturation,[80] and immune cell migration, apoptosis, and phagocytosis through the production of specific short-chain fatty acids. [81] G. vaginalis , a facultative anaerobe, has been shown to produce sialidases, which are capable of inactivating local IgA.…”
Section: The Human Microbiotamentioning
confidence: 99%
“…St. John and colleagues compared the effects of vaginal fluid from women with bacterial vaginosis or healthy controls on monocyte-derived dendritic cells. Fluids from women with bacterial vaginosis, but not controls, induced production of IL-12, IL-23, increased expression of dendritic cell activation markers (HLA-DR, CD40 and CD83) and stimulated proliferation of T-cells in allogeneic mixed lymphocyte reactions41. Chancroid is one of the STDs most closely associated with HIV transmission, perhaps due to extensive disruption of the epithelial barrier, bleeding and recruitment of susceptible cells42.…”
Section: Sexually Transmitted Infections Alter the Mucosal Microenvirmentioning
confidence: 99%